514 F1-taught Orthopaedic Teaching for Students (FOTS). (12th October 2021) - Hashmi, Y; Kumar, P R; Beedham, W
Abstract: Introduction: F1 doctors, despite being expected to teach, have had reduced opportunity to do so during COVID-19. Medical students have also become increasingly concerned for upcoming exams due to time away from placements. A national orthopaedic teaching programme was designed to provide F1 doctors with opportunities to develop their teaching skills and synergistically improve students' confidence in performing clinical orthopaedic examinations. Method: A University Trauma & Orthopaedics society coordinated the teaching programme consisting of 6-weekly online sessions on each joint examination (shoulder, hip, knee, hand, ankle and lumbar spine). Each session was delivered by two F1 tutors. Pre- and post-session MCQs were provided to students to assess improvement in knowledge. Anonymous feedback forms were also disseminated. Results: From the 341 students that attended, 87.1% provided feedback. 86.2% felt that they had de-skilled due to time off, with a mean 15 weeks off from placement. Based on a 5-point Likert scale, students displayed a mean improvement in confidence (1.9±1.1, p < 0.001) and MCQ scores (1.4±1.3, p < 0.001) before and after the sessions. 91.6% of students agreed that the use of online teaching increased attendance. Of the 10 tutors, all reported improvement in confidence to teach and teaching skills. Conclusions: We demonstrate that online delivery of clinical orthopaedic examinations is effective and present our findings to encourage similar teaching programmes to be adopted at other locations and specialities.